Ethical reasoning at work: A cross-country comparison of gender and age differences - Karin Lasthuizen; Kamal Badar (Administrative Sciences, 2023)
This paper uses the IBE Ethics at Work 2018 survey to explore employees' ethical reasoning and examine gender and age differences across 12 countries. Debates about gender and ethics have been intense since Kohlberg's theory of moral development, with feminist critiques from Gilligan and others advocating the different voice of women, while the recent arrival of Millennials in the workplace has raised new questions about age/generational differences and ethics. The findings in this study suggest that women and older workers have stronger ethical judgments in the workplace than men and younger workers. These gender and age differences, both among employees and managers, are consistent across countries. This study shows that individual characteristics are important for employees' ethical reasoning, which affects their ability to make ethical decisions and act ethically. Business ethics research should therefore take greater account of differences between (groups of) employees and their learning needs when examining the effectiveness of ethics policies and instruments, while organizations can improve employee ethical reasoning by adopting diversity-based training programs and ethical leadership.
Keywords: 350; gender; age; ethical reasoning; global employee survey; organizational ethics